Bistability analysis of thermal effects in nonlinear microresonator waveguide / Nurul Fathinah Azrisham, Mohammad Amirul Hairol Aman and Ahmad Fakhrurrazi Ahmad Noorden - Azrisham, Nurul Fathinah; Hairol Aman, Mohammad Amirul; Ahmad Noorden, Ahmad Fakhrurrazi (Faculty of Applied Sciences, 2023)
An analytical simulation of a nonlinear all-pass microring resonator (MRR) was performed based on ambient temperature and ring radius variation. The optical transfer function (OTF) of the MRR was obtained using the coupling theory formulation. The OTF was used to simulate the output spectrum of the MRR system. In this research, the thermal and ring radius effects on the bistable spectrum of the system were analyzed because low thermal stability and big ring radius are major impediments to utilizing bistability properties for various applications. The optimization of the bistable spectrum was executed by determining the suitable configuration of MRR based on the variation of temperatures and ring radii to obtain the largest switching power. The simulation results demonstrate that the MRR system using the ring radius of 3 μm at the temperature of 300 K yields the highest switching power with the optimized system. The optimization analysis was further done by investigating the solution for the MRR system when using a large ring radius and at low temperatures, which is a problem in achieving better bistability performance.